2002
DOI: 10.1097/00042737-200208000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Role of partner's infection in reinfection after Helicobacter pylori eradication

Abstract: Recurrence of H. pylori infection seems to be relatively infrequent, even if the patient's spouse is H. pylori-positive. The molecular study demonstrated that the strains in reinfected patients and their partners are different, suggesting that the patient's partner does not act as a reservoir for H. pylori reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
3
26
1
2
Order By: Relevance
“…As siblings rarely cohabit as adults and strains are rarely passed between spouses (43,44), this suggests that strains were acquired during childhood, as has been shown for other populations (41,42). This therefore implies that H. pylori strains possessing type s1/m1 vacA were acquired before the development of gastric atrophy and hypochlorhydria and suggests that the association between toxigenic strains and these conditions is likely to be causal.…”
Section: Discussionmentioning
confidence: 77%
“…As siblings rarely cohabit as adults and strains are rarely passed between spouses (43,44), this suggests that strains were acquired during childhood, as has been shown for other populations (41,42). This therefore implies that H. pylori strains possessing type s1/m1 vacA were acquired before the development of gastric atrophy and hypochlorhydria and suggests that the association between toxigenic strains and these conditions is likely to be causal.…”
Section: Discussionmentioning
confidence: 77%
“…The number of children in the household has been proposed as a risk factor for infection in parents (21), and in childless couples transmission between spouses was not supported (27). Other rather small studies have found no association between the number of children and the parents' infection status (12,32).…”
Section: Discussionmentioning
confidence: 82%
“…Our PubMed search yielded 10 studies of H. pylori recurrence conducted in developed countries [4][5][6][7][8][9][10][11][12][13], and 7 studies conducted in developing countries [14 -20] that used the 13 CUBT at eradication and follow-up and otherwise met our inclusion criteria. Table 1 summarizes the studies from the developed countries, and Table 2, the studies from the developing countries.…”
Section: Resultsmentioning
confidence: 99%